MultiWii Based Quadcopter by Using Arduino Controller - Chong, Yen Fang; Najib Mohammed Ahmed Al-Fadhali (Progress in Engineering Application and Technology, 2023)
In this study, we examine the design and development of a quadcopter drone, which is a type of unmanned aircraft that can take off and land vertically and is controlled by radio equipment and self-programming devices. Quadcopters are equipped with four motors that use variable thrust to control the aircraft’s lift and allow for PID control of its roll, pitch, yaw, and thrust. The main components of a quadcopter include a flight controller with integrated accelerometers and gyroscope sensors, brushless DC motors with propellers, a transceiver module, and other parts. The transceiver module allows the transmitter to send control signals to the receiver, while the flight controller’s sensors detect acceleration and angular rates based on the pitch, yaw, and roll angles. However, we found that the quadcopter’s open-source MultiWii software was not compatible with its hardware components. Through this study, we hope to increase our understanding of the structure of unmanned aerial vehicles and how to develop a quadcopter that is able to receive the control signal from the transmitter and perform a stable flight.